The Desire that Propels Entrepreneurial Intentions - Hernan E. Riquelme; Abdullah Al Lanqawi (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The purpose of this paper is to integrate conceptual and empirical work on the prediction and explanation of entrepreneurial intentions. Specifically, it tests a model that accounts for the motivation of the entrepreneur, a salient factor commonly omitted in current theories of entrepreneurial intentions. We test the role of entrepreneurial desire (a distinct concept from desirability) as a determinant of two distinctive entrepreneurial intentions. This research corroborates recent findings that highlight the importance of identifying intentions to start a business with an orientation for growth as opposed to income substitution. Further, while the role of emotions has become an important factor in entrepreneurship, anticipated emotions have received very little attention in the prevailing literature. Using a sample from Kuwait, this paper finds that desire is a stronger predictor of growth-oriented intentions than income-substitution intentions. Also, entrepreneurial desire partially mediates the effects between attitude, anticipated emotions and entrepreneurial intentions.